Decision Support System For Employee Bonus Determination With Web-Based Simple Additive Weighting (SAW) Method In PT. Mayatama Solusindo - Yuda Irawan (Journal of Applied Engineering and Technological Science (JAETS), 2020)
Decision Support System is a computerized system designed to increase effectiveness in decision making to solve semi-structured and unstructured problems so that the decision-making process can be of higher quality. One method of solving MADM problems is by using the Simple Additive Weighting method. The SAW method is to find the weighted sum of the performance ratings for each alternative of all attributes. This study aims to design and create a system to determine which employees are entitled to receive bonuses, for that we need a decision support for giving employee bonuses decisions. In this study using the Simple Additive Weighting method. The system development model used is a waterfall. Waterfall has several stages, namely needs analysis, system design, writing program code, program testing, program implementation and maintenance. The results showed the benefits of the SAW method as a decision support system for determining employee bonuses based on the employee performance of PT. Mayatama Solusindo can assist administrators in determining employee bonuses quickly and effectively. So the bonus that employees get using the SAW method is the basic salary times the percentage of the ranking value.